Embracing the Fog of War Assessment and Metrics in Counterinsurgency - Connable, Ben (RAND Corporation, 2012)
The unpredictable counterinsurgency environment challenges centralized, quantitative campaign assessment. A comprehensive examination of the centralized, quantitative approach to assessment, as described in the literature and doctrine and applied in two primary case studies (Vietnam and Afghanistan), reveals weaknesses and gaps and proposes an alternative process: contextual assessment.